Enhanced visible-light photocatalytic activity of one dimensional In2O3/In2TiO5 nanobelts. (May 2019) - Zhang, Qinku; Zhou, Jianhua; Dai, Qilin; Yan, Yonghua; Yao, Binghua; Ng, Chuck Chuan; Han, Fengxiang; Ma, Meng; Cheah, Pohlee; Proctor, Georgio; Hu, Mengge
Graphical abstract: Schematic illustration showing photocatalytic mechanism of In2 O3 /In2 TiO5 photocatalyst under simulated sunlight irradation. Highlights: One dimensional In2 O3 /In2 TiO5 nanobelts with the width of approximate 550 nm and thickness of 140 nm were successfully synthesized. In2 O3 /In2 TiO5 nanobelts with the mole ratio of 1–10 exhibited the highest photocatalytic activity under simulated sunlight irradiation. The skeleton of levofloxacin (LEV) was completely destroyed after irradiation for 60 min and the degradation rate of RhB reached 97.1% in 120 min. The photocatalytic activity was still above 85% after 5 cycles. In2 O3 /In2 TiO5 not only have an excellent visible-light-driven photocatalytic activity, but also can be used in organic dye removal and antibiotics wastewater treatment. Abstract: In this study, a two-step synthesis route combining an electrospinning with a precipitation process was used to prepare one dimensional In2 O3 /In2 TiO5 nanobelts. The obtained In2 O3 /In2 TiO5 nanobelts were characterized with XRD, SEM, EDS, UV–vis DRS and N2 adsorption-desorption isotherms. Effects of the mole ratios of In2 O3 to In2 TiO5 on the photocatalytic activity of photocatalyst were investigated using rhodamine B (RhB) as a model pollutant. Results showed that In2 O3 /In2 TiO5 nanobelts with the mole ratio of 1–10 exhibited the highest photocatalytic activity under xenon lamp (150 W) irradiation. The degradation rate of RhB reached 97.1% in 120 min, and the photocatalytic degradation followed the first order kinetic model. Furthermore, the skeleton of levofloxacin (LEV) was completely destroyed after irradiation for 60 min. The recycling tests confirmed that the photocatalytic activity was still above 85% after 5 cycles. This proved that In2 O3 /In2 TiO5 not only had an excellent visible-light-driven photocatalytic activity, but also could be used in organic dye removal and antibiotics wastewater treatment.